(untitled) (Eurasian Journal of Philology Science and Education, 2019)
Personal names are not just labels put on individuals, they are symbols that reflect the cultural and historical context and location, denote gender, class, ethnicity, and religion. Names and their display have a potent effect on people’sjudgments and life as well. Authors see proper names as located atbetween the world of our thoughts, beliefs and desires andthe world of our actions, institutions, and practice. Thus the study of changing first names is a way to explore social processes in urban Kazakhstan. The aim of this study is to track changes in naming practices of ethnic Kazakhs, both Kazakh-speaking and Russian-speaking, residing in Almaty. This paper include a wide review of the literature as Kazakhstani and foreign authors regarding naming traditions, changing realities in anthroponyms and their meaning. Paper draws upon more than 1,700 personal names collected from three generations of 61 participants (students of local universities) currently residing in Almaty. Quantitative and qualitative analysis of the data shows the main factors that have influenced the traditional practice of naming in Kazakh culture were identified. The study revealed that there is a distinct change in the choice of names across generations. The names became shorter, there are fewer names containing specific name suffixes (e.g., -bai, - bek, - gali/qali, -geldi/keldi, -myrza etc.) and specific Kazakh sounds, more female names are explicitly marked for gender, etc. There are also differences in naming practices between Kazakh and Russian-speakers as well as differences in male and female name preferences. Analysis of changing naming practices reveal current social processes of social distinction and uncover symbolic ethnicity, class, gender, religion-based cultural boundaries in Kazakhstan. The study demonstrates that examining names as cultural indicators and indicators of social change could be a fruitful line of inquiry for studying socio-cultural change.